MIRERC 076/2025: Assessment of Factors Influencing Outcome of Drug-Resistant Tuberculosis Treatment Among Patients Enrolled in Meru County, Kenya - Muthuri Koome , Dr. Geoffrey; Dr. Patrick K. Kubai; Dr. Dorothy Kagendo Kithinji (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Globally, the World Health Organization (WHO) reported that a total of 175, 923 cases of drug-resistant Tuberculosis were notified in 2023 with Africa, being among the regions that contribute to a substantial proportion of the cases globally. Kenya being among the 30 high burden countries with a huge burden of both drug-susceptible and drug-resistant Tuberculosis. Drug-resistant tuberculosis is a major cause of morbidity and mortality across population demographics. Although there has been availability of treatment which has saved millions of lives globally, drug-resistant tuberculosis treatment outcome remain sub-optimal globally. The World health organization reported that only 63 percent of drug-resistant tuberculosis cases enrolled in 2020 were successfully treated with 13 percent mortality and a loss to follow-up of 11 percent. In Kenya, only 67 percent of all cases enrolled in 2020 were cured against a national target of 90 percent. Meru County is among the counties in Kenya harboring a high burden of both drug-susceptible and drug-resistant Tuberculosis reported 348 cases of drug-resistant Tuberculosis between 2020 and 2023. Treatment outcomes remain sub-optimal with the county achieving an average of less than 90 percent treatment success rate, mortality rate of 4 percent and loss to follow-up of 6 percent among patients reported in the 2020 to 2023 cohort. Treatment for drug-resistant tuberculosis is complex and often requires intensive patient monitoring so as to achieve optimum treatment success. This study aims to assess the factors influencing the outcome of drug-resistant tuberculosis treatment among patients enrolled in Meru County, Kenya. Specifically, the study will assess the patient characteristics, the clinical factors and health service delivery factors influencing the outcome of drug-resistant Tuberculosis treatment. A retrospective cohort study design will be used to assess the variables of patient characteristics, healthcare service delivery factors and clinical factors and their influence on treatment outcomes. Data from records of patients enrolled in health facilities within Meru County between January 2020 and December 2023 will be analyzed. Study data will be collected by use of a structured data collection tool and analyzed using the Statistical Package for Social Sciences (SPSS) version 28.0. Descriptive and inferential statistics will be utilized to describe relationships between the independent and the dependent variables. Bivariate and multivariate analysis will be done by use of regression models and associations will be interpreted using Chi square test. Study data will be presented using tables, graphs and charts. The study results will be significant in informing policy and practices aimed at enhancing the quality of care offered to patients with drug-resistant Tuberculosis